Policies versus perception: estimating the impact of drought awareness on residential water demand - Stone, Janine, author; Goemans, Christopher G., advisor; Constanigro, Marco, committee member; Sharvelle, Sybil E., committee member (Colorado State University. Libraries, 2011)
In response to the water shortages of 2002, Colorado utilities adopted numerous policies promoting water conservation. However, despite this demand-management emphasis, utilities are still distinguishing between the impacts of conservation programs and the psychological impacts of the drought itself. That is, water managers are unsure if post-drought decreases in water consumption are solely due to utility-controlled policies or if they result from a combination of drought awareness and/or permanent changes in water-use behaviors. For this reason, gauging the effectiveness of conservation policies requires answering the following: First, did awareness of the drought lead consumers to conserve more water than predicted, given utility policies alone? Next, if drought awareness did influence demand, is continued awareness--as opposed to utility policies or permanent changes in water use--the reason water demand has failed to return to pre-drought levels? To answer these questions, this research estimates an econometric water demand model using billing data from a major Colorado utility. Results show that drought awareness did decrease water demand both during and after the height of the drought; however, baseline demand still appears to be trending downward even after we control for both drought awareness and utility policies.